Legal exegesis about security - Rivera Alfaro, Ronald Gerardo (2012)
In this article I try to show from different dimensions -structural, contractual and legal policy- how has been called security as an exclusive right of law. The actually subsumed to the prevention of crime and punishment mechanisms needed to promote exclusive. Those new epistemological ways analyze the security strip of these moments and spaces that have been ritualized by the semantic power. All of that making and altering the meaning of security to insecurity. This increases the tension and uncertainty budget through media coverage of some events criminals that cause the perception of insecurity increases disproportionately in relation to actual crime.